Gender differences in the social consequences of unemployment: how job loss affects the risk of becoming socially isolated - Eckhard, Jan (Sage, 2022)
Using longitudinal data from the German Socio-Economic Panel, the study examines whether the impact of unemployment on the risk of becoming socially isolated is different for women and men and whether it can be traced back to financial straits. An isolating effect of unemployment is found only with regard to men, to long-term unemployment, and to social isolation in terms of scarce contact to friends and family. There is no such effect with regard to women, to short-time unemployment, and to social isolation in terms of a non-participation in civic associations. It is also found that the isolating impact of unemployment is only to a small extent attributable to the financial situation of the unemployed.
In: Work, Employment and Society, 36 (2022), Nr. 1. pp. 3-20. ISSN 0950-0170 (Druck-Ausg.); 1469-8722 (Online-Ausg.)